2017
DOI: 10.2147/oajc.s134124
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates of patient–provider family planning discussions among HIV-infected pregnant women in South Africa

Abstract: Patient–provider family planning discussions and preconception counseling can reduce maternal and neonatal risks by increasing adherence to provider recommendations and antiretroviral medication. However, HIV-infected women may not discuss reproductive intentions with providers due to anticipation of negative reactions and stigma. This study aimed to identify correlates of patient–provider family planning discussions among HIV-infected women in rural South Africa, an area with high rates of antenatal HIV and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Furthermore, the study found an association between discussing family planning with a health care provider and fertility intentions, as in previous research. 60 These findings have been confirmed in several other studies, 5 , 6 and show the importance of the South African Department of Health guidelines in helping facilitate the initiation of discussions about fertility intentions by health care providers with PLHIV. In contrast, family planning knowledge and participation in an enhanced PMTCT intervention, which included information on family planning, were associated with decreased fertility intention.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, the study found an association between discussing family planning with a health care provider and fertility intentions, as in previous research. 60 These findings have been confirmed in several other studies, 5 , 6 and show the importance of the South African Department of Health guidelines in helping facilitate the initiation of discussions about fertility intentions by health care providers with PLHIV. In contrast, family planning knowledge and participation in an enhanced PMTCT intervention, which included information on family planning, were associated with decreased fertility intention.…”
Section: Discussionsupporting
confidence: 55%
“…Surprisingly, IPV during the perinatal period, unplanned pregnancy, time since HIV diagnosis, and depression (analysis not shown) were not associated with fertility intentions, contrary to previous research. 60 Future research should examine the relative trade-offs in reproductive decision making among this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, however, in rural Mpumalanga, only a quarter of HIVinfected women had discussed family planning with their providers. [73] There are substantial drug interactions between efavirenz and Implanon, considerably reducing drug levels of etonogestrel, the active drug in Implanon. [74][75][76] Interactions between efavirenz and Jadelle appear even more pronounced than with Implanon.…”
Section: Cmementioning
confidence: 99%
“…The literature on HIV and FP integration includes interventions targeting providers [9][10][11][12], HIV+ patients [13][14][15], and discordant couples [16,17] as well as efforts to enhance male involvement [18][19][20]. In heterosexual populations with a high prevalence of HIV, an important target audience for HIV and FP services is couples who can benefit from joint services [21][22][23].…”
Section: Introductionmentioning
confidence: 99%